Uso de fontes alternativas de água não potável em edificações multifamiliares de Vitória, Vila Velha e Serra : por que não? - Gomes, Carla Cordeiro (2018)
According ONU statistic, water scarcity accounts over 40% of the world's population, and the Metropolitan Region of Grande Vitória enters this statistic when in 2016, due to drought, when water rationing was necessary. Based on this scenario, the question